Development of a robotic endoscopic sinus surgical device - Kumaravel Kandaswamy. (2009)
Development of various kinds of surgical device and endoscopes that can be successfully employed in minimally invasive surgery is an emerging research area because of its wide application in advanced surgical techniques. Moving ahead, to develop a robotic surgical device is demanding but is more friendly to the surgeons and patients than the conventional surgical system this can avoid adverse blood and tissue loss to the infected patients especially by the use of intelligent motion control systems. This dissertation aims to understand the current technique used in Functional Endoscopic Sinus Surgery (FESS), and attempts to design and develop a prototype robotic endoscopic sinus surgical device. The methodology involves concept generation, design development, kinematic and performance analysis. The proposed prototype includes flexible 2-Degree Of Freedom (DOF) steerable shaver. The flexible shaver has flexible drive shaft system which can transmit rotation at a desired torque, efficiently to the operating site. An automated robotic aim is designed and fabricated to control the steering angle of the distal end of the shaver. This device can provide sufficient operating range for the efficient removal of polyps and to open the air obstruction deep in to the intraturbinate stoma. An important feature which makes this prototype unique and successful compared with earlier models, is its ability to control and freeze the steering angle by a self locking worm assembly. Various experimental investigations were carried out on the prototype’s performance with respect to its steering angles with promising results.